META-ANALYSIS OF THE EFFECT OF APPLYING PROBLEM BASED LEARNING MODEL ON PHYSICS LEARNING - Annisa Hidayatul Adha; - Festiyed (PILLAR OF PHYSICS EDUCATION, 2022)
The development of education is one aspect that must always consider. One of the endeavor to raise educational standards is to develop the curriculum. The real conditions obtained after conducting the analysis showed that the learning model applied was conventional, which resulted in low learners' learning outcomes. One solution to this problem is to use a paradigm of problem-based learning (PBL) in physics learning. Meta-analysis research systematically examines statistical techniques by combining the results of several previous studies to determine the overall conclusions. The investigation intends to ascertain the application models of PBL have an influence in physics learning. This method examines some results from several articles on similar problems. This method accumulates the impact of insignificant article results into a significant result. The results obtained from the meta-analysis method can answer the gaps in the results of various articles with similar problems. The research results revealed that PBL Model are being used in physics learning as a whole has an influence and is suitable to apply in learning with an effect size of 0.777. PBL Model significantly influence the class level, subject matter units, concept understanding skills, critical thinking, creative thinking, solution to problem, and mastery of knowledge aspects. This article's conclusion study is to apply the PBL model in physics learning more effectively to improve learners' learning outcomes.